Pusaka pavilion: urban acupuncture as narrative pathway to relive history - Santosa, Gitta Ramania; Utami, Adinda Sih Pinasti Retno (Journal of Placemaking and Streetscape Design, 2023)
Pabean Market is known as one of the legacies of Dutch colonialism in Surabaya. The constant hustle and bustle of fishmongers, customers, fish laborers, distributors, to commodity trucks remains to this present day. More often than not, architectural history or cultural heritage of the site go unnoticed or forgotten. To evoke the sociocultural context and involve the community in its preservation, the design also utilizes mobilization or circulation as a narrative strategy. The author focuses on “Storytelling for Forgotten History, Vehicles for Cultural Heritage”, aimed at supporting the commercial activities without leaving historical memory through movement experiences. Utilizing the Force-Based Framework and analyzing the sociocultural context, culture, and needs of the site, the design proposal focuses on storytelling and cultural heritage preservation. The categorization of movement types allows for the determination of suitable media of modules to facilitate effective circulation within the designed environment. Pusaka Pavilion serves as a medium to optimize movement, enabling individuals to experience history, encounter new perspectives, and immerse themselves in diverse cultures. This article presents the conceptual framework and design approach to reflect forgotten history, revive cultural contexts, and foster an inclusive engaging environment.